2003
DOI: 10.1515/znb-2003-0127
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium Dichloride Coordination by Nitrogen Donor Molecules

Abstract: The reaction of anhydrous beryllium chloride with nitrogen donors L in diethylether as a solvent under mild conditions affords 1:2 complexes of the type L2BeCl2 [L = benzonitrile (1), pyridine (2), 3,5-dimethylpyridine, pyrrolidine, piperidine (8), and diethylamine (10)]. Structural studies of compounds 1, 2, 8 (CHCl3), and 10 have shown that the complexes have the beryllium centers N2Cl2- tetracoordinated with a distorted tetrahedral geometry of the core unit. In crystals of 8 and 10 these molecules are assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 0 publications
3
36
0
4
Order By: Relevance
“…In the 9 Be NMR spectra ( Figure S8 in the Supporting Information), we always observed a triplet at 1.5 ppm with 1 J BeF = 35 Hz, which shows that two fluorine atoms are bound to the beryllium atom. In the 19 F NMR spectra ( Figure S9 in the Supporting Information), a quartet at À164.5 ppm was observed, which is due to the 3 = 2 spin of 9 Be. The 1 J FBe coupling constant was found to be 34 Hz.…”
Section: A C H T U N G T R E N N U N G (M-oh) 3 a C H T U N G T R E Nmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 9 Be NMR spectra ( Figure S8 in the Supporting Information), we always observed a triplet at 1.5 ppm with 1 J BeF = 35 Hz, which shows that two fluorine atoms are bound to the beryllium atom. In the 19 F NMR spectra ( Figure S9 in the Supporting Information), a quartet at À164.5 ppm was observed, which is due to the 3 = 2 spin of 9 Be. The 1 J FBe coupling constant was found to be 34 Hz.…”
Section: A C H T U N G T R E N N U N G (M-oh) 3 a C H T U N G T R E Nmentioning
confidence: 99%
“…Both calculated values agree well with the experimentally observed value. The chemical shift of 19 F was calculated to be À192 and À169 ppm at the PBE0/TZVP and CCSD(T)/cc-pVTZ levels of theory, respectively. 3 or ND 3 , respectively, showed N À H/D stretching vibrations in the expected regions (Table S3 in the Supporting Information), which are redshifted relative to free NH 3 /ND 3 due to the coordination of NH 3 /ND 3 to Be 2 + and NÀH/D···F hydrogen bonding.…”
Section: A C H T U N G T R E N N U N G (M-oh) 3 a C H T U N G T R E Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these complexes may not be very stable, two of them, namely H 2 CvCHPH 2 : BH 3 and HCuCPH 2 : BH 3 , have already been synthesized and spectroscopically characterized, 35,36 and some rather stable complexes between N-bases and BeCl 2 have also been reported. 37 In our study we will consider not only the possibility of losing the proton from the XH 2 group but also from the BH 3 or BeH 2 ones. Since, it would be interesting to know whether unsaturation has some significant effect on the phenomena to be investigated, we have also included a series of saturated ethyl derivatives as a suitable reference.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Recent work has suggested that Be binding occurs through the displacement of strong hydrogen bonds. [19] Strong hydrogen bonds occur when the distance between the two heteroatoms, typically OÀH···O or OÀH···N, is shorter than the sum of the van der Waals radii and the energy barrier to hydrogen transfer between two atoms is on the order of the O À H vibrational zero-point energy.…”
mentioning
confidence: 99%